2022
DOI: 10.3390/bs12070227
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing EFL Learners’ Self-Efficacy Beliefs of Learning English with Emoji Feedbacks in CALL: Why and How

Abstract: Encouraging feedback positively affects learners’ self-efficacy; in language learning, self-efficacy predicts language learner performance and behavior. Our research involved three studies to expand knowledge about why and how we can enhance English as a Foreign Language (EFL) learners’ self-efficacy beliefs in online settings. In Study 1, based on an online survey with 310 participants, we ascertained the extent to which EFL learners with greater self-efficacy tend to challenge themselves by learning content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 78 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…Thus, improving self-efficacy may be important to developing listening ability. Furthermore, previous studies (e.g., Chen, 2007;Rahimi and Abedi, 2014) demonstrated the strong links between self-efficacy, metacognition, and listening ability. Metacognition can regulate the relationships between selfefficacy and listening comprehension (Siegel, 2014).…”
Section: Self-e Cacy and L Listeningmentioning
confidence: 68%
See 3 more Smart Citations
“…Thus, improving self-efficacy may be important to developing listening ability. Furthermore, previous studies (e.g., Chen, 2007;Rahimi and Abedi, 2014) demonstrated the strong links between self-efficacy, metacognition, and listening ability. Metacognition can regulate the relationships between selfefficacy and listening comprehension (Siegel, 2014).…”
Section: Self-e Cacy and L Listeningmentioning
confidence: 68%
“…The results showed that online listening tasks can contribute to increased vocabulary and information retention than text-based tasks. However, in the study of Chen and Zhang (2010), instruction with online learning systems did not surpass traditional listening instruction in improving Chinese EFL learners' listening comprehension. Thus far, few studies have delved into metacognitive intervention in an online setting, especially drawing on the Metacognitive Pedagogical Cycle.…”
Section: Online L Listening Researchmentioning
confidence: 80%
See 2 more Smart Citations
“…Students with high speaking self-efficacy more actively participated in class, studied harder, and demonstrated less adverse emotional reactions when encountering problems (Darmawan et al, 2021). In a survey involving 310 participants, Chen and Hsu (2022) reported that EFL learners with a higher level of self-efficacy tended to challenge themselves with learning content that required higher proficiency, which results in better language skill development.…”
Section: Self-efficacymentioning
confidence: 99%